PENGARUH MODEL PEMBELAJARAN TPACK BERBANTUAN ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV - ellyarisvamargolang; Kiki Aryaningrum; Juaidah Agustina (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine the effect of the TPACK learning model assisted by assemblr edu on student learning outcomes in science learning for grade IV. This study is a quantitative experimental research design pre-experimental design in the form of one group pretest-posttest design. The sample in this study was grade IV of SD Negeri 1 Mukti Sari totaling 37 students. The data collection technique used was a test. Based on the results of the study, the average pretest score was 45.68 and the average posttest score was 74.66. Furthermore, based on the results of the t-test analysis using the paired sample t-test, the Sig (2-tailed) value was 0.000 so it can be concluded that 0.000 <0.05 indicates that Ho is rejected and Ha is accepted. Thus, there is a significant effect of the use of the TPACK learning model assisted by assemblr edu on student learning outcomes in science learning for grade IV.